2011
DOI: 10.1007/s11250-011-9922-1
|View full text |Cite
|
Sign up to set email alerts
|

Contagious caprine pleuropneumonia in Beetal goats

Abstract: Seroprevalence, clinical findings, and lesions of contagious caprine pleuropneumonia (CCPP) in Beetal goats were recorded during an outbreak. The overall seroprevalence of CCPP was 32.50%. Confirmation of Mycoplasma mycoides in serum was carried out using counter immunoelectrophoresis (CIE) technique. The highest CIE-positive cases were recorded in the older goats (51.72%) as compared to young ones. Nasal swabs collected from 39 goats showing respiratory signs were found positive for M. mycoides. The most cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
4
18
1
Order By: Relevance
“…The methanolic leaf extract of T. terrestris had alkaloids, tannins, saponins and glycosides. This agrees with Hussain et al (2011) who reported the reducing sugar, anthraquinone, flavonoids, saponins, tannins, alkaloids and glycosides in stem, leaves and fruits of T. terrestris. Similar results were also observed by Kianbakht and Jahanianiian (2003) who reported that methanolic extracts (fruits, stems , leaves and roots) of T. terrestris growing in Iran inhibited the growth of S. aureus, E. faecalis, E. coli and P. aeruginosa and plant showed considerable activity against all bacteria.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The methanolic leaf extract of T. terrestris had alkaloids, tannins, saponins and glycosides. This agrees with Hussain et al (2011) who reported the reducing sugar, anthraquinone, flavonoids, saponins, tannins, alkaloids and glycosides in stem, leaves and fruits of T. terrestris. Similar results were also observed by Kianbakht and Jahanianiian (2003) who reported that methanolic extracts (fruits, stems , leaves and roots) of T. terrestris growing in Iran inhibited the growth of S. aureus, E. faecalis, E. coli and P. aeruginosa and plant showed considerable activity against all bacteria.…”
Section: Resultssupporting
confidence: 93%
“…Terpenoids were found in the methanolic extract of P. harmala. These results agree with Siddiqui et al (2009) Hussain et al (2011) who reported the reducing sugar in stem, leaves and fruits of T. terrestris. Phenolics were found in the methanolic extract of P. harmala.…”
Section: Phytochemical Screeningsupporting
confidence: 93%
“…Treatment has reduced morbidity and mortality to 16.66% and 9.16% against 100% and 66.66% respectively. Hussain et al (2012) reported a mortality of 9.17% due to CCPP. Ravishankar et al (2011) showed 62.5% antimycoplasma antibodies on rapid plate agglutination test in goats.…”
Section: Prevalence Morbidity Mortalitymentioning
confidence: 99%
“…Fever, anorexia, depression, coughing, nasal discharge, lagging, lying down, pleurodynae (thorax pain), arthritis, mastitis, keratoconjuctivits, nervousness and loss of body weight are the constellation of signs usually exhibited in mycoplasma infections and noted in different diseases in sheep and goat Priya et al, 2008;Ingle et al, 2008;Awati & Chavhan 2013;Abraham et al, 2015;Sheikh et al, 2016;Yatoo & Kanwar, 2016). The most consistent clinical findings of mycoplasmosis are mild to severe cough, purulent nasal discharge, emaciation, dyspnea, increased respiration rate, and pyrexia (Hussain et al, 2012). Mycoplasma pneumonia in goats were characterized by rise of temperature (40-43•C), marked depression, tremor, reluctance to move, painful accelerated respiration, cough, partial to complete closure of nostril, nasal discharge, anorexia, low tone bleating, recumbency and few cases of arthritis and corneal opacity.…”
Section: Clinical Signs Of Mycoplasmosismentioning
confidence: 99%
“…Nothing has been mentioned regarding CCPP in the articles of Zahur et al (2006) and Afzal (2010), published in the Pakistan Veterinary Journal which has been wrongly cited in a literature review as a report on CCPP. Hussain et al (2012) isolated Mycoplasma mycoides from sick goats showing respiratory symptoms with 9.17% mortality and the respiratory disease was given the name CCPP; this does not comply with the classical definition of CCPP.…”
Section: The Term Contagious Caprine Pleuropneumonia Is Erroneously Umentioning
confidence: 99%